ANALISIS KINERJA KEUANGAN PADA PT. TEMPO SCAN PACIFIC TBK - Sianturi, Lita Selviana (EKONOMIA, 2017)
PT. Tempo Scan Pacifik Tbk started its pharmaceutical product trading business since 1953. PT Tempo Scan Pacifik Tbk was established through a restructuring process in 1991 and originally named PT Scanchemie which in 1970 started commercial production of pharmaceutical products on a large scale. Along with the passage of time, the Company started its subsidiary producing cosmetics products and consumer products since 1977. The problems raised, whether the financial performance of PT. Tempo Scan Pacific Tbk has increased in 2015 compared to 2014. Viewed from the ratio of liquidity, profitability and solvency. The purpose and usefulness in this research is to know the financial performance of PT. Tempo Scan Pacifik Tbk and provide theoretical views to the leader of PT Tempo Scan Pacifik Tbk as supporting in decision making. The research data used as the analysis is the income statement of 2014 and 2015 and the balance sheet of 2014 and 2015. The method of problem solving used is the liquidity ratio seen from Current Ratio (Decrease Current) decreased in 2014 by 300.22% compared to 2015 Amounted to 253.76%, seen from the Cash Ratio (Cash Ratio) decreased in 2014 sebsar 118.03% compared to the year 2015 of 102.33%. Solvency ratio seen from the Debt to Total Assets Ratio has increased in 2014 by 27.23% compared to the year 2015 of 30.97%. Profitability ratio seen from the Return on Assets Ratio decreased in 2014 by 10.44% compared to the year 2015 8.42%. Based on the results of analysis and discussion, it can be seen from the ratio of liquidity, solvency and profitability decreased and increased but still within the limits of good performance. This can be seen from the liquidity ratio of PT Tempo Scan Pacific Tbk can guarantee its debts that will soon mature using assets owned. While seen from solvency ratio of PT. Tempo Scan Pacifik Tbk is experiencing an increase in its assets, and profitability ratios in PT Tempo Scan Pacific Tbk each year earn a profit.